ANALISIS PENGARUH KINERJA PELAYANAN TERHADAP LOYALITAS PASIEN DENGAN KEPUASAN PASIEN SEBAGAI VARIABEL MODERASI PADA RUMAH SAKIT UMUM ISLAM YAKSSI GEMOLONG, SRAGEN - Setyaningsih Sri Utami, Desi Ratnawati, Edi Wibowo & (Universitas Slamet Riyadi, 2016)
The objective of the research are to analyses (1) the effect of service performance to patient loyalty of RSUI Yakssi Gemolong. (2) the effect of patient satisfaction to patient loyalty of RSUI Yakssi Gemolong. (3) the effect of patient satisfaction in moderation the service performance to patient loyalty of RSUI Yakssi Gemolong. Population of this research is all of RSUI Yakssi Gemolong patients during Desember 2015, and taken a sample of 70 respondents. Data collection technique used questionnaire that through stages of testing the validity dan reliability test. Test requirements regression using classic assumption test. Data were analyzed using absolute difference test. The conclusion of each hypothesis test results show that (1) the service performance does not have a significant effect to patient loyalty of RSUI Yakssi Gemolong, is proven by probability value of t test result 0,08 > 0,05. (2) patient satisfaction have a significant effect to patient loyalty of RSUI Yakssi Gemolong, , is proven by probability value of t - test result (0,000) < 0,05. (3) patient satisfaction does not moderated the service performance to patient loyalty of RSUI Yakssi Gemolong, it is proven by probability value of absolute difference test result 0,155 > 0,05.Keywords: service performance, patient satisfaction, patient loyalty